KARYA PUTU SUTAWIJAYA SEBUAH REFLEKSI ATAS TUBUH - Didung Putra Pamungkas (SULUH: Jurnal Seni Desain Budaya, 2021)
Reading Putu Sutawijaya's painting entitled "Single Energy" portrays the body as a central focus, through documentation, and direct observation through his painting which is then analyzed using Roland Barthes's semiotic approach, genealogy of body Foucault, Phenomenology ponty, Heidegger's Existentialism, and Freud's Psychoanalysis. Roland Barthes's semiotic approach divides signs in denotation and connotation. At the level of denotation, Putu is describing the movements of figures with the burden that surrounds them. At the level of connotation explains that the burden on social systems and value systems, binding and not dehumanizing people. Then Foucault explained the body as a soft body. Putu shows that there is no aspect of freedom possessed by free humans in their own bodies. Phenomenology Ponty, the world has been available for individuals. So human relations and their world are never truly distant, but are dialectical. Heidegger's existentialism, saw the relationship of the body with his world. In his paintings, Putu sees culture as always constructing a person, showing the form of one's relationship with his world. Freud's psychoanalysis of libido, as a form of individual freedom to actualize itself, but is always limited by rules, values and norms, Putu's work illustrates that there are efforts to escape, but are still charged by social considerations. With the study of this painting it is hoped that it can stimulate enthusiasm in creating art and enrich new discourses in the world of Indonesian art.